A study of hypoglycemic activity of acids and salts containing 1,2,4-triazole - Dovbnia, D. V.; Frolova, Yu. S.; Kaplaushenko, A. H.; Довбня, Дмитро Віталійович; Фролова, Юлія Сергіївна; Каплаушенко, Андрій Григорович (My University, 2023)
This article presents the study results of the hypoglycemic properties among 1,2,4-triazole derivatives synthesized at the Department of Physical and Colloidal Chemistry of the Zaporizhzhia State Medical University. Today, many people have a sedentary way of life, also most of their diet contains products that they frequently use, which increase the level of glucose in the blood, which can provoke the development of serious diseases. Therefore, to date, the creation of drugs that exhibit hypoglycemic activity and have a low level of toxicity remains an urgent task for medicine and pharmacy. In the first stage of our research, acute toxicity prediction was performed. The hypoglycemic activity of the synthesized compounds was assessed by performing an intraperitoneal glucose tolerance test (IPGTT) with a change in the blood glucose concentration of the animal after its single intraperitoneal administration in the form of a 40% solution at a dose of 2 g/kg of rat body weight. Thirty-eight compounds of the different classes were studied for hypoglycemic activity. Zinc (II) 2-{5-[(3,4-methoxyphenyl)-3H-1,2,4-triazole-3-yl]thio} acetate (3.18) showed the highest efficiency in terms of the ability to lower blood glucose levels, namely, by 27.3% (approximately 1.3 times).
Keywords: 1,2,4-triazole; hypoglycemic activity; intraperitoneal glucose tolerance test